Postcolonial criticism: literary aspect of Ukrainian literary studies - Mariya Chobanyuk; Чобанюк Марія; Chobanyuk Mária (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. This article examines certain phenomena in modern Ukrainian literature and culture that can be described as postcolonial. Special attention is given to the transformations that distinguish these phenomena from the previous cultural system, as well as to the features and particularities of postcolonial criticism as a literary methodology.It is noted that postcolonial criticism is a branch of contemporary literary studies that emerged in the English-speaking world in the late 1970s. It arose from the integration of the most influential approaches of deconstruction, psychoanalysis, Marxism, new historicism, and feminism, while also taking into account the historical and cultural models of countries that had liberated themselves from colonial rule. Postcolonial criticism addresses issues such as ethnicity, national identity, cultural universality, cultural hybridity and difference, as well as the problems of language and historical interpretation. A decisive role in the development of postcolonial theory was played by the work of Edward Said, an American scholar of Arab origin, particularly hisbook Orientalism.The article emphasizes the importance of distinguishing between two types of cultural opposition to colonialism: anticolonial and postcolonial. The anticolonial stance involves direct resistance to colonialism, centred around genuine ideals of national liberation. The postcolonial perspective, however, goes beyond a simple rejection of colonialism and affirmation of its opposite. It involves a deeper awareness and critical engagement, characterized by the use of both colonial and anticolonial experiences and a recognition of the relativity of these two historical frameworks.Political scientists primarily regard colonialism as a system through which the colonizer gains and maintains power over the colonized, compelling the latter to act inthe interests of the former. Economists, in contrast, highlight the subordination of the colonized territory’s economy to that of the colonizer, particularly in terms of benefiting the colonizer in the global market. Cultural colonialism refers to the deployment of cultural institutions and ideologies–whether in popular or elite culture–that support political and economic domination.Postcolonial discourse in Ukrainian culture has emerged relatively recently. A noticeable postcolonial trend has been present in Ukrainian literature for some time, as evidenced by the works of Ivan Dziuba, MarkoPavlyshyn, Oleh Ilnytskyi, Myroslav Shkandrij, Mykola Riabchuk, among others. Postcolonial criticism in general –and Ukrainian postcolonial criticism in particular –is marked by the overcoming of the inferiority complex. This is vividly reflected in the themes of contemporary literary studies: national self-criticism, the development of national self-awareness, the peculiarities of the Ukrainian mentality, the concept of “great literature”, and the global context of Ukrainian writing. Special attention is given to the writers’ focus on the affirmation of national consciousness.

Резюме. У цій статті розглядаються певні явища в сучасній українській літературі та культурі, які можна було б назвати постколоніальними. Звертається особлива увага на трансформації, що відрізняють їх від культурної системи, що панувала раніше, а також на особливості та специфіку постколоніальної критики як літературознавчої методології. Зазначено, що постколоніальна критика –це напрям сучасного літературознавства, який виник в англомовному світі наприкінці 70-х років на базі інтеграції кращих досягнень деконструктивізму, психоаналізу, марксизму, нового історизму, фемінізму з урахуванням історичних і культурологічних моделей країн, що звільнилися від колоніального ярма. Постколоніальна критика порушує проблеми етнічності, національної ідентичності, культурної універсальності, культурної гібридності та культурної відмінності, проблеми мови, історії. Вирішальну роль у створенні теорії постколоніальної критики відіграла праця американця арабського походження Едварда Саїда «Орієнталізм». У статті звернено увагу на те, що доцільно розрізняти два види протистояння колоніалізму в культурі –антиколоніальний та постколоніальний. Антиколоніальнимварто вважати звичайний опір колоніалізму, де центральне місце займають справжні ідеї національного визволення. Постколоніальним можна вважати протистояння не на рівні простого заперечення колоніалізму й схвалення протилежного, а й на рівні усвідомлення. Постколоніальному ставленню притаманне використання досвіду як колоніального, так і антиколоніального, й розуміння відносності цих двох історичних структур.Політологи розглядають колоніалізм насамперед як сукупність заходів, завдяки яким колонізатор перебирає і реалізовує владу над колонізованим, примушуючи його діяти згідно з рішеннями і в інтересах колонізатора; економісти натомість убачають його основну рису в підкоренні економіки колонізованої території проблемам колонізатора, зокрема в його вигоді на світовому ринку. Культурний колоніалізм –це комплекс заходів культурних установ та ідеологій у будь-яких випадках популярної чи високої культури, спрямований на підтримку політичної та економічної влади. Наголошено на тому, що постколоніальний дискурс в українській культурі виник порівняно недавно. Існує вже деякий час і помітна постколоніальна течія в українській літературі. Про це свідчать праці Івана Дзюби, Марка Павлишина, Олега Ільницького, Мирослава Шкандрія, Миколи Рябчука та інших. Постколоніальну критику взагалі, а українську зокрема, характеризує подолання комплексу меншовартості. Яскраве свідчення цього –теми сучасних літературознавчих досліджень: національна самокритика, проблеми виховання національної самосвідомості, риси української ментальності, концепція «великої літератури», світовий контекст українського письменства. Увагу привертає спрямованість письменників на самоствердження національної свідомості.

A tanulmány a kortárs ukrán irodalom és kultúra bizonyos jelenségeit vizsgálja, amelyek posztkoloniálisnak nevezhetők. Az elemzés külön figyelmet fordít azokra az átalakulásokra, amelyek megkülönböztetik ezeket a jelenségeket az előző kulturális rendszertől, valamint a posztkoloniális kritika irodalmi módszertanának jellemzőire és sajátosságaira.Megállapítást nyert, hogy a posztkoloniális kritika a kortárs irodalomtudomány egyik irányzata, amely angol nyelvterületen alakult ki az 1970-es évek végén. A dekonstrukció, a pszichoanalízis, a marxizmus, az új historicizmus és a feminizmus legmeghatározóbb megközelítéseinek integrációjából jött létre, figyelembe véve azoknak az országoknak a történelmi és kulturális modelljeit, amelyek megszabadultak a gyarmati uralomtól. A posztkoloniális kritika olyan kérdésekkel foglalkozik, mint az etnicitás, a nemzeti identitás, a kulturális egyetemesség, a kulturális hibriditás és különbözőség, valamint a nyelv és a történelem értelmezésének problémái. A posztkoloniális elmélet kialakulásában döntő szerepet játszott Edward Said, arab származású amerikai tudós munkássága, különösen az Orientalizmuscímű könyve.Az elemzés hangsúlyozza, hogy meg kell különböztetnünka gyarmatosítás elleni kulturális ellenállás két típusát: az antikolonializmust és a posztkolonializmust. Az antikolonialista álláspont a gyarmatosítással szembeni közvetlen ellenállást jelenti, amelynek középpontjában a nemzeti felszabadulás valódi eszméi állnak. A posztkoloniális szemlélet viszont túlmutat a gyarmatosítás egyszerű elutasításán: mélyebb tudatosságot és kritikai viszonyulást foglal magában. Jellemzője, hogy egyaránt felhasználja a gyarmati és az antikolonialista tapasztalatokat, és felismeri e két történelmi struktúra relativitását.A politológusok elsősorban olyan rendszerként tekintenek a gyarmatosításra, amelyben a gyarmatosító megszerzi és fenntartja a hatalmat a gyarmatosított felett, és arra kényszeríti, hogy a saját érdekei szerint cselekedjen. A közgazdászok ezzel szemben a gyarmatosított terület gazdaságának a gyarmatosító gazdasági érdekeinek való alárendeltségét hangsúlyozzák, különösen a haszonszerzés tekintetében. A kulturális gyarmatosítás a kulturális intézmények és ideológiák olyan működését jelenti –akár a populáris, akár a magas kultúrában –, amely a politikai és gazdasági uralom fenntartását szolgálja.A posztkoloniális diskurzus az ukrán kultúrában viszonylag nemrégiben jelent meg. Az ukrán irodalomban már egy ideje megfigyelhető egy posztkoloniális irányzat, amit olyan szerzők munkái is bizonyítanak, mint Ivan Dziuba, Marko Pavlyshyn, Oleh Ilnytskyi, Myroslav Shkandrij, Mykola Riabchuk és mások. A posztkoloniális kritika általában –és különösen az ukrán posztkoloniális kritika –az alsóbbrendűségi komplexus leküzdésével jellemezhető. Ez élénken tükröződik a kortárs irodalomtudomány témáiban: a nemzeti önkritika, a nemzeti öntudat kialakításának problémái, az ukrán mentalitás sajátosságai, a „nagy irodalom” koncepciója, valamint az ukrán irodalom világkontextusa. Külön figyelmet érdemel az írók nemzeti tudat megerősítésére irányuló törekvése.
Постколоніальна критика: літературознавчий аспект українського літературознавства
Posztkoloniális kritika: az ukrán irodalomtudomány irodalmi aspektusa
https://aab-philologica.kmf.uz.ua/aabp
Keywords: postcolonial criticism; culture; system; methodology; world context; literary studies